Systemowe ciśnienie tętnicze w praktyce lekarza okulisty – wybrane aspekty - Budzyński, Jacek; Pulkowski, Grzegorz (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
Blood pressure have the dual importance in eye-doctor practice. Its high values, leading to injury of vascular wall, cause its stiffness, narrowing and eye-ball perfusion disturbance. On the other hand, in case of impaired eye-ball circulation autoregulation, recurrent episodes of low blood pressure may lead to processes of ischemia-reperfusion with oxygen free radicals overproduction and retinal ganglion cells apoptosis. It seems, that complex control of the atherosclerosis risk factors level as well as use of drugs favourable affecting endothelial function (angiotensin-converting enzyme inhibitor, statins), may decrease an eye-ball vasculature injury and make it less susceptible to blood pressure variation. This suggests acceptance of atherosclerosis risk factors, especially hypertension, as a predictor of early glaucomatous optic neuropathy on the “pre-perimetric” stage of disease.